Х₁*х₂=28 х₁+х₂=-р х₁-х₂=2 тогда х₁=2+х₂ Подставим х₁=2+х₂ в выражение х₁+х₂=-р (2+х₂)+х₂=-р 2+2х₂=-р 2(1+х₂)=-р 1+х₂=-р/2 х₂=(-р/2) -1 Подставим этот результат в х₁=2+х₂ х₁= 2 + (-р/2) -1==1-р/2 Найдем теперь произведение х₁*х₂=28 х₁*х₂=(1-р/2)*(-р/2) -1)=28 решая это равенство,получаем (р/2)² - 1=28 (р/2)² =28+1=29 р²/4=29 р²=4*29=116 р=√116=√4*29=2√29
х₁+х₂=-р
х₁-х₂=2 тогда х₁=2+х₂ Подставим х₁=2+х₂ в выражение х₁+х₂=-р
(2+х₂)+х₂=-р
2+2х₂=-р
2(1+х₂)=-р
1+х₂=-р/2
х₂=(-р/2) -1 Подставим этот результат в х₁=2+х₂
х₁= 2 + (-р/2) -1==1-р/2
Найдем теперь произведение х₁*х₂=28
х₁*х₂=(1-р/2)*(-р/2) -1)=28
решая это равенство,получаем (р/2)² - 1=28
(р/2)² =28+1=29
р²/4=29
р²=4*29=116
р=√116=√4*29=2√29